2018
DOI: 10.3390/e20060432
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Scaling in Systems of Natural Cities

Abstract: Hierarchies can be modeled by a set of exponential functions, from which we can derive a set of power laws indicative of scaling. The solution to a scaling relation equation is always a power law. The scaling laws are followed by many natural and social phenomena such as cities, earthquakes, and rivers. This paper is devoted to revealing the power law behaviors in systems of natural cities by reconstructing the hierarchy with cascade structure. The cities of America, Britain, France, and Germany are taken as e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Because POIs provide services for the surrounding population within the city, this paper supposes utilizing service area as the basic natural city units based on Reilly's Law of Retail Gravitation [19], although there exist differences in service capacities, the vast number of POIs make it possible to ignore the influence, which makes Thiessen polygons able to present its service area. According to the heavy tail and self-organized feature of such polygons in the context of urban complex systems [41], the principle of maximum entropy is implemented to seek the critical value which mostly influences the deviation of service areas. As the maximum entropy shows the same distribution as a normal distribution, the 3σ principle of Gaussian distribution is also tested to achieve an appropriate threshold value for extracting the service area polygons.…”
Section: Discussionmentioning
confidence: 99%
“…Because POIs provide services for the surrounding population within the city, this paper supposes utilizing service area as the basic natural city units based on Reilly's Law of Retail Gravitation [19], although there exist differences in service capacities, the vast number of POIs make it possible to ignore the influence, which makes Thiessen polygons able to present its service area. According to the heavy tail and self-organized feature of such polygons in the context of urban complex systems [41], the principle of maximum entropy is implemented to seek the critical value which mostly influences the deviation of service areas. As the maximum entropy shows the same distribution as a normal distribution, the 3σ principle of Gaussian distribution is also tested to achieve an appropriate threshold value for extracting the service area polygons.…”
Section: Discussionmentioning
confidence: 99%
“…The development of an urban system is complex system engineering, involving different spatial scales [ 46 , 47 , 48 ]. In addition to location, overall regional structure, and other related factors, the optimization of individual urban internal structure is closely related to the overall strength of regional urban system self-organization [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the variance of the error model, we propose the urban scaling law model considering heterogeneity as: The conditional probability in this method can be computed as: where Based on the definition of the maximum-likelihood fitting method, the likelihood function can be written as: that is: In order to maximize the likelihood function, we log-transformed the Equation (20) as: The joint probability density function can be expanded as: where denotes the prior probability of the urban population. The prior probability can be obtained by the maximum entropy statistics of the urban system [ 52 , 53 ]. However, it can be suggested that is independent of any of estimators of urban scaling law.…”
Section: The Chvr Methodsmentioning
confidence: 99%